Incidence of Hyperoxia and Excess Oxygen Use in Critically Ill Pediatric Patients - Nawaz, Hira; Gova, Murtaza Ali; Waqas, Muhammad; Asif, Afshan; Siddique, Uzma; kayani, Aasma (Biological and Clinical Sciences Research Journal, 2025)
Hypoxia is a very well-known risk factor for poor outcomes in patients admitted to intensive care units. Objective: This study aims to determine the prevalence of Hyperoxemia and the duration of Excess oxygen use in patients with hyperoxemia through chart review. Methodology: This prospective observational study was conducted in the Pediatric Intensive Care Unit (PICU) of the National Institute of Child Health (NICH) from December 2023 till December 2024. Data were collected prospectively using a structured case report form explicitly developed for this study (attached in the appendix). Information recorded included demographic details such as age and gender, clinical variables including admitting diagnosis, presence of comorbidities, and type of respiratory support received (HFNC or MV). Hourly oxygenation data, specifically FiO₂ and SpO₂ values, were documented over the first 24 hours of PICU admission. Results: 28% of patients (56/200) experienced hyperoxemia, with the majority requiring mechanical ventilation (60.7%). Patients with hyperoxemia had a significantly higher median FiO₂ (0.65, IQR: 0.55–0.75) compared to those without hyperoxemia (0.45, IQR: 0.40–0.55, p<0.001) and a longer duration of oxygen therapy, with 71.4% of hyperoxemic patients receiving oxygen for more than 12 hours compared to 40.3% of those without hyperoxemia (p=0.002). Respiratory illness was more common in the hyperoxemia group (64.3% vs. 41.7%, p=0.01). Conclusion: It is concluded that hyperoxemia and excess oxygen use are common among critically ill pediatric patients receiving oxygen therapy, particularly in the first 24 hours of admission to the PICU. A significant proportion of patients, especially those with respiratory illnesses and those on mechanical ventilation, were exposed to high oxygen levels despite having elevated oxygen saturation levels.